Navigating Scholarly Development Through a CoP: #generational-lenses - Carol A Olszewski MA; Toni M Paoletta MEd; Keli B Pontikos MA; Matthew L Selker MPA; Kyle A Znamenak MA; Catherine A Hansman PhD (Adult Education Research Conference, 2018)
CoPs provide opportunity for professional identity exploration. Extant research neglects how multiple identities, including generational memberships, influence development. This study explores professional identity development of scholars within a multigenerational CoP.
Keywords: CoP; multigenerational; professional identity development